Genomic variability within laboratory and wild isolates of the trichostrongyle mouse nematode heligmosomoides polygyrus - Abu-Madi, M.A.; Reid, A.P.; Lewis, J.W.; Mohd-Zain, S.N. (2000)
PCR-RFLP techniques have been used to characterize wild and laboratory isolates of the trichostrongyle nematode Heligmosomoides polygyrus from the wood mouse Apodemus sylvaticus and the laboratory mouse Mus musculus respectively. Both isolates can be distinguished by eight endonuclease digestions of the ITS region of the rDNA repeat namely, Alu I, Dde I, Hpa II, Hae III, Hinf I, Hha I, Pvu II and Sal I. In two of the digests, Hinf I and Rsa I, a minor polymorphism was observed in the wild isolate of H. polygyrus which has been cultured in laboratory-bred A. sylvaticus for several generations when compared with H. p. polygyrus from wild A. sylvaticus. A minor polymorphism was also identified in further wild isolates of H. polygyrus collected from A. sylvaticus in a field site in Egham, Surrey. However no evidence of polymorphism was observed in the laboratory isolate of H. polygyrus from the CD1 strain of M. musculus and the laboratory-bred A. sylvaticus. Reasons for this are discussed and further studies on the population genetics of H. polygyrus are suggested.